Bosnia and Herzegovina : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bosnia and Herzegovina. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that the economic growth in Bosnia and Herzegovina is expected to rebound to more than 2 percent in 2015, as economic activity is picking up in Europe. Industrial activity and exports have been gathering momentum. Domestic political risks weigh heavily on the outlook. The risk of policy slippages and delays in implementation of the Reform Agenda is significant given the complex political set up and the strong opposition to reforms from vested interests. On the external side, risks are more balanced, as stagnation in Europe, possible financial market strains, or geopolitical tensions could dampen growth, while a faster recovery in Europe or the resolution of trade issues with the European Union could spur exports.